Sample collection and sample handling errors submitted to the transfusion error surveillance system, 2006 to 2015. Issue 7 (17th April 2018) - Strauss, Rachel; Downie, Helen; Wilson, Ann; Mounchili, Aboubaker; Berry, Brian; Cserti‐Gazdewich, Christine; Callum, Jeannie
Abstract : BACKGROUND: In Canada, transfusion‐related errors are voluntarily reported to a tracking system with the goal to systematically improve transfusion safety. This report provides an analysis of sample collection (SC) and sample handling (SH) errors from this national error‐tracking system. STUDY DESIGN AND METHODS: Errors from 2006 to 2015 from 23 participating sites were extracted. A survey was conducted to obtain information regarding institutional policies. Samples received in the blood bank were used to calculate rates. "Wrong blood in tube" (WBIT) errors are blood taken from wrong patient and labeled with intended patient's information, or blood taken from intended patient but labeled with another patient's information. RESULTS: A total of 42, 363 SC and 14, 666 SH errors were reported. Predefined low‐severity (low potential for harm) and high‐severity errors (potential for fatal outcomes) increased from 2006 to 2015 (low SC, SH: 13‐27, 3‐12 per 1000; high SC, SH: 1.9‐3.7, 0.5‐2.0 per 1000). The WBIT rate decreased from 12 to 5.8 per 10, 000 between 2006 and 2015 (p < 0.0001). The overall WBIT rate was 6.2 per 10, 000, with variability by site (median, 0.3 per 10, 000; range, 0‐17 per 10, 000). Sites with error detection mechanisms, such as regrouping second sample requirements, had lower error rates than sites that did not (SC, SH: 12, 1 per 1000 samples vs. 17, 3 per 1000 samples; p < 0.0001). CONCLUSION: WBIT rates decreased significantly. Low‐severity error rates are climbing likely due to increased ascertainment and reporting. Prevention studies are necessary to inform changes to blood transfusion standards to eliminate these errors.